The Fib rinolytic Therapy in Renal Disease - Kishimoto, Thiharu; Mithunami, Kenithi; Hatori, Toshio; Oguma, Shigeru; Haniu, Thunehisa; Tornimoto, Kazuhiko; Kaburagi, Thuneo; Takayama, Shinithi; Yoyoyama, Shoithi; Tanaka, Kazunari; Suzuki, Toyosaka (The Japanese Journal of Nephrology, 1980)
1) Twenty-nine cases of renal diseases were administrated intravenously 30, 000 units/day of urokinase during 2 weeks. Urinary volume, urinary protein, urinary blood cells, blood urea nitrogen, serum creatinine, renal function, FDP in urine and blood, and fibrinogen in plasma before and after urokinase therapy were observed.2) Twelve cases were effective for urokinase therapy. GFR increased in 7 cases, urinary protein decr-eased in 10 cases and urinary red cells decreased in 5 cases.3) Eight cases in effective cases for urokinase therapy were taken renal biopsy. In these histological findings, 5 cases were proliferative glomerulonephritis, 2 cases were membranoproliferative glomerulon-ephritis and 1 case was membranonephropathy.4) In 2 cases of acute renal failure, after urokinase therapy GFR increased with diuresis. And, in pati-ents with pregnancy kidney, after urokinase therapy urinary protein and urinary blood cells decreased.5) In many cases that were effective for urokinase therapy, FDP in morning urine was positive. How ever, in chronic renal failure in which FDP in urine was posititve, urokinase therapy was non-effective.